Unlovely Seeds: Human/Nature/Wilderness in Isabella Valancy Crawford’s Winona; or, The Foster-Sisters - Jackson-Harper, Renée Suzanne (Pivot: A Journal of Interdisciplinary Studies and Thought, 2019)
In 1872, Isabella Valancy Crawford answered a call printed in George-Édouard Desbarats’s weekly story paper the Hearthstone seeking: “narratives, novels, sketches penned by vigorous Canadian hands, welling out from fresh and fertile Canadian brains, thrilling with the adventures by sea and land, of Canadian heroes” (Early and Peterman 25). Crawford’s winning submission to the Hearthstone’s call, Winona; or, The Foster-Sisters, reaps the materials for its narrative from “inexhaustible fields” of both “fact and fancy” of a burgeoning Canadian national imagination (25). This paper is interested in exploring the specifically Canadian anxieties expressed by the novel, as this paper examines the manner in which the displaced occupants of the novel’s Howard lodge act as uncanny avatars of the natural world and of a wilderness as they resist (or, are denied) a place in the domestic space established by the “national family” (167). In this paper, I argue that Crawford’s Winona, with its attention to both domestic and natural spaces, provides a productive site through which to interrogate the vexed relationship of a newly Confederated country with its own “native materials” (Johnson 7; Early and Peterman 10).